Effect of Aging on Retinal Nerve Fiber Layer Thickness in Normal Asian Indian Eyes: A Longitudinal Study. (2nd January 2017) - Mansoori, Tarannum; Balakrishna, Nagalla
ABSTRACT: Purpose : To determine longitudinal retinal nerve fiber layer (RNFL) thickness measurement change with aging, after a period of 3 years using spectral optical coherence tomography/scanning laser ophthalmoscope (OCT/SLO). Methods : A total of 50 eyes of 25 normal subjects underwent RNFL thickness measurement in 2008 and again in 2011 by a single operator, using spectral OCT/SLO. Measurements were compared at baseline and at follow-up. Linear mixed model analysis was used to measure the effect of age on RNFL thickness measurements over the 3 years. Results : Mean RNFL thickness was 107.92 ± 11.1 µm in 2008 and 106.56 ± 10.8 µm in 2011. For every year increase in age, mean RNFL thickness showed a statistically significant decrease by −0.54 µm (95% confidence interval, −0.76 to −0.31; p < 0.0001). There was a statistically significant loss of peripapillary RNFL thickness in most RNFL regions, except for the temporal quadrant ( p = 0.37) and corresponding 7, 8, 9, and 10 o'clock hour sectors ( p = 0.72, 0.75, 0.17, 0.14, respectively). Conclusion : RNFL thickness as measured by spectral OCT/SLO decreased significantly with advancing age over a period of 3 years, and was not uniform across the four quadrants. This age-related variation should be taken into account in RNFL thickness measurements when evaluating patients for diagnosis and follow-up of glaucoma.